2019
DOI: 10.1111/1471-3802.12476
|View full text |Cite
|
Sign up to set email alerts
|

The role of primary school teachers’ attitudes and self‐efficacy beliefs for everyday practices in inclusive classrooms – a study on the verification of the ‘Theory of Planned Behaviour’

Abstract: Within the framework of implementing inclusive education in primary schools, various questions arise concerning the role of teachers’ personal resources in their everyday practices in heterogeneous classrooms. Teachers’ professional personalities as well as their intentions concerning inclusive teaching are considered to be important prerequisites for successful learning environments. Therefore, we examined the relevance of primary school teachers’ personal resources, such as their attitudes towards inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 26 publications
5
34
3
4
Order By: Relevance
“…However, looking at the factors of teacher attitudes separately, neither teachers' perception of their behavior management nor their perception of their ability to teach in inclusive classrooms, which should to some extent represent the behavioral dispositions of teachers, predicted their classroom management practices. These results support the finding of Hellmich et al (2019) indicating no significant relationship between self-efficacy beliefs and self-reported teaching practices. However, the lack of significant effect in the present study could be due to the unidimensional assessment of attitudes toward inclusion with the ORI questionnaire (Ewing et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…However, looking at the factors of teacher attitudes separately, neither teachers' perception of their behavior management nor their perception of their ability to teach in inclusive classrooms, which should to some extent represent the behavioral dispositions of teachers, predicted their classroom management practices. These results support the finding of Hellmich et al (2019) indicating no significant relationship between self-efficacy beliefs and self-reported teaching practices. However, the lack of significant effect in the present study could be due to the unidimensional assessment of attitudes toward inclusion with the ORI questionnaire (Ewing et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, teachers' attitudes toward inclusion had also no indirect effect-via teachers' classroom management-on student social acceptance. These study findings indicate that the attitudes of teachers toward inclusion might be less important than has been suggested by many cross-sectional studies (e.g., de Boer et al, 2012;Desombre et al, 2019;Hellmich et al, 2019) and that its impact on teaching practices is overestimated. Studies have found that teachers with more teaching experience in inclusive classrooms hold more positive attitudes toward inclusion (De Boer et al, 2011).…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…This psychological theory explains individuals’ behaviour through their subjective norms, attitudes and perceived behavioural control. Additionally, within the study of Hellmich, Löper, and Görel (2019), the theory of planned behaviour was used as theoretical framing to examine the associations between teachers’ attitudes and self‐efficacy beliefs towards inclusive education and use of inclusive teaching practices in the classroom. Teachers’ attitudes towards inclusive education can be defined as 'a psychological tendency that is expressed by evaluating a particular entity with some degree of favor or disfavor' (Eagly and Chaiken, 1993, p. 1).…”
Section: Introductionmentioning
confidence: 99%